Impact of Covid-19 Patients with Diabetes Mellitus and its Association with Clinical Outcomes - Karki, Manoj; Chaudhary, Shatdal; Jaiswal, Niraj Kumar; Rayamajhi, Bidhata; Gautam, Narayan; Shrestha, Jharana; Khan, Mahmud Alam; Chhetri, Pradip (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION COVID-19 is a debilitating disorder affecting lungs with multiple organs. Diabetes mellitus is considered as a common co-mor- bidity whose impact has not been fully understood. There is a hypothesis that patients with diabetes are at increased risk of severe disease or death due to COVID-19. The main objective of the present study was to ﬁnd the the association of COVID-19 diabetes mellitus (DM) and non-diabetes mellitus patients with the clinical outcomes. MATERIAL AND METHODS This cross-sectional study was conducted in hospitalized patients with COVID-19 at Universal College of Medical Sciences (UCMS), Bhairahawa. Total of 200 patients were enrolled in the study period from July 2021 to January 2022 whose clinical proﬁle, socio-demographic and biochemical variables were assessed. The study variables taken were symptoms, random blood glucose (RBG), glycosylated hemoglobin (HbA1c) and their outcomes like High Dependency Unit/Intensive Care Unit (HDU/I- CU) or COVID ward admission, hospital stay and mortality. RESULTS A total of 40% of the patients require HDU/ICU hospitalization with 20% requiring ventilator support. The ﬁndings revealed a strong link between diabetes mellitus and fatigue (p=0.012) as well as mortality (p=0.032). The difference in hospital stay between ventilator and non-ventilator groups was substantial (p=0.001). The hospital stay in the mortality group was signiﬁcantly shorter (p=0.026). Likewise, RBG and HbA1c are higher than in the non-mortality group (189 vs 167; 5.7 vs 5.6 %). CONCLUSION Hypertension and diabetes are the most common morbidities associated with COVID-19 individuals. Diabetes mellitus was found to have a substantial link to fatigue, but there was no link between HbA1c and the length of hospital stay or the method of ventilation.